Assessment of common wheat (Triticum aestivum L.) yield and quality under organic farming in the southwest of Romania - Ioana C. DUNĂREANU; Gheorghița L. PISCANU; Dorina BONEA; Mihai BOTU (Notulae Botanicae Horti Agrobotanici Cluj-Napoca, 2023)
Taking into account the rising demand for organic wheat and the need to guarantee both high productivity and quality of the crops, the choice of cultivar plays a crucial role. These intended objectives may solely be attained by employing the most appropriate cultivars for organic agriculture. The aim of this study was to evaluate the suitability of 15 wheat cultivars for cultivation in organic farming according to three important parameters for organic farmers and processors, namely grain yield, test weight and protein content. The field experiment took place over two consecutive growing seasons, in the center of the Oltenia region (southwest of Romania) under organic farming conditions. The results showed significant effects of the climatic conditions in the year of study, but also of the cultivar on all studied parameters. The effect of genotype-environment interactions was significant only for test weight and protein content. On average, over the two years of study, the grain yield was 3899 kg ha-1, the test weight was 70.8 kg hl-1, and the protein content was 10.1%. The recently released cultivar ‘Voinic’ obtained the maximum grain yield (4755 kg ha-1) and also a maximum test weight and protein content (73.9 kg hl-1, respectively 10.7%). In conclusion, it follows that by using cultivars suitable for organic farming, good and quality yields can be obtained that can be a suitable raw material for baking industry.